Production of highly enantioselective (−)-menthyl butyrate using Candida rugosa lipase immobilized on epoxy-activated supports - Othman, Siti Salhah; Basri, Mahiran; Hussein, Mohd Zobir; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Jasmani, Halila (Elsevier, 2008)
Optically active (−)-menthyl butyrate was synthesized by enantioselective esterification of racemic (±)-menthol and butyric anhydride using lipase from Candida rugosa immobilized onto epoxy-activated supports of Eupergit C and Eupergit C 250 L through physical adsorption method. The effects of various temperature, storage condition, stability in organic solvent and lipase recyclability were investigated for their influence on the enzymatic enantioselective formation of (−)-menthyl butyrate. The immobilized lipases retained high catalytic activity of up to 31% yield and 100% enantiomeric excess of the desired product, and showed better stability compared to the native lipase. They also exhibited about 50% retained activity even after incubation at higher temperatures, storage at room temperature and after long incubation in hexane. Immobilized lipases also showed considerably efficient reusability.